Fracture of the tibia after a fibula graft for mandibular reconstruction: A rare complication, report of a case. Issue 5 (24th May 2021) - Goey, Ru‐shan; van Drunen, Bert; van der Linden, Enrike; van Merkesteyn, J.P. Richard
Abstract: A tibia fracture after a fibula harvest is a rare and serious condition; however, when treated adequately, it has a good outcome. The possibility of a fracture should be kept in mind and other pathology and/or metastasis should be ruled out. Abstract : A tibia fracture after a fibula harvest is a rare and serious condition; however, when treated adequately, it has a good outcome. The possibility of a fracture should be kept in mind and other pathology and/or metastasis should be ruled out.